Identification of the Diversity of Indigenous Arbuscular Mycorriza Fungi in the Rhizosphere of Coffee (Coffea Sp) Arabica Solok Radjo West Sumatera - Armansyah Armansyah; Eti Farda Husin; Indra Dwipa; Faly Sandika; Reski Marbeni Putra (Green Engineering Society, 2022)
Arbuscular mycorrhizal fungi are a group of fungi that can be symbiotic with many types of plants. Soil factors and plant species, affect the diversity of arbuscular mycorrhizal fungi. Likewise, differences in location and rhizosphere cause differences in the diversity of species and populations of AMF. In addition, not all AMF have the same morphological and physiological characteristics, therefore it is very important to know their identity. Coffee is a plant that has economic value and the potential for symbiosis with AMF. This study aimed to identify AMF in the rhizosphere of four varieties of Solok Radjo coffee plants in the Aia Cold area of ​​the Gumanti Valley, Solok, West Sumatra. Meanwhile, the stages of this research include: collecting and collecting data in the field, determining the location of the soil sample, analyzing soil properties in the laboratory, isolating AMF spores, and identifying AMF spores morphologically. The results showed that the diversity of AMF spores was found in 3 genera, namely Glomus sp., Acaulospora sp., and Gigaspora sp. The Kartika coffee variety has a higher AMF spore population than Sigararutang, Andongsari and Gayo.